Interconnectivity and metacommunication - Hayet Bahri; Robert Williams (Peoples' Friendship University of Russia (RUDN University), 2017)
The study of interpersonal communication touches on a range of different disciplines, each with its own focus. This has given rise to an apparent fragmentation in the literature which is manifested in the categorisation of the various components of a communicative act, and even the subdivision of the categories established. This can be seen in the study of metacommunication, which although considered an essential component of human interaction has been subdivided into a myriad of constituent parts. Whilst the separation of various components permits detailed focus on different facets of interpersonal interaction, there is a risk that the complementarity of the various facets may be underestimated or even lost. To autonomise each aspect of a communicative act may not be conducive to a comprehensive understanding of what happens in an interaction since all elements, verbal, non-verbal and contextual, to name but a few, need to be considered and interpreted simultaneously. Approaches to the study of metacommunication, whilst being multidimensional, appear to have led to fragmentation. It is our contention that understanding what constitutes a complete communicative interaction involves the consideration of these various aspects at the same time. Starting from the position that no category exists in a vacuum and is part and parcel of a whole communicative act, this study considers a more holistic approach to communication as an adjunct to the current tendency for separation. To illustrate this method, the article identifies various aspects and categories within the area of metacommunication and examines the convergence and potential divergence within them. Through the case study of silence as a communicative act that appears to bridge various subdivisions, this paper argues for an umbrella conceptualisation that unifies rather than compartmentalises the various aspects of metacommunication.